Ocular Manifestations of Coronavirus Disease 2019 (COVID-19): Its Remedy and Prevention - Bhattarai, Sanjeev (Nepal Mediciti Medical Journal, 2022)
SARS-CoV-2 is a Coronavirus that causes COVID-19 with mild to severe respiratory illness. It is highly contagious disease transmitted through direct or indirect contact with infected people or contaminated surfaces mainly through respiratory droplets. Several research articles are published which evaluated the ocular findings in patients with Coronavirus disease 2019. Commonly patients are suffering from initial ocular symptoms followed by systemic symptoms of the disease. Transmission even from the ocular surface could be possible via tears and other secretions through eyes. The most frequently noted initial symptom of COVID-19 is follicular conjunctivitis with acute and diffuse bilateral red eye. Similarly other ocular manifestations include eye Corneal sub epithelial infiltrates with epithelial defects,episclerits,acute anterior Uveitis, Retinitis, Optic neuritis, Cataract, Vitreous hemorrhages and cranial nerve palsies. As a remedy for ocular manifestation, orally administered Ribavirin has been used in vision threatening cases. For mild to moderate ocular symptoms ,antihistaminic eye drops with ocular lubricating drops and cool compress are till now applied. To be in safe side and to prevent the transmission from the ocular surfaces, all eye care practitioners are advised to wear personal protective equipment including gowns, gloves, masks and face shields during the ophthalmic procedures.